Cucumber Ribosomal Protein CsRPS21 Interacts With P22 Protein of Cucurbit Chlorotic Yellows Virus - Yang, Xue; Wei, Ying; Shi, Yajuan; Han, Xiaoyu; Chen, Siyu; Yang, Lingling; Li, Honglian; Sun, Bingjian; Shi, Yan (Frontiers in Microbiology, 2021)
Cucurbit chlorotic yellows virus (CCYV) is a cucurbit-infecting crinivirus. RNA silencing can be initiated as a plant defense against viruses. Viruses encode various RNA silencing suppressors to counteract antiviral silencing. P22 protein encoded by RNA1 of CCYV is a silencing suppressor, but its mechanism of action remains unclear. In this study, the cucumber ribosomal-like protein CsRPS21 was found to interact with P22 protein in vitro and in vivo. A conserved CsRPS21 domain was indispensable for its nuclear localization and interaction with P22. Transient expression of CsRPS21 in Nicotiana benthamiana leaves interfered with P22 accumulation and inhibited P22 silencing suppressor activity. CsRPS21 expression in N. benthamiana protoplasts inhibited CCYV accumulation. Increasing numbers of ribosomal proteins are being found to be involved in viral infections of plants. We identified a P22-interacting ribosomal protein, CsRPS21, and uncovered its role in early viral replication and silencing suppressor activity. Our study increases knowledge of the function of ribosomal proteins during viral infection.